(Im)mobilization of arsenic, chromium, and nickel in soils via biochar: A meta-analysis. (1st October 2021) - Arabi, Zahra; Rinklebe, Jörg; El-Naggar, Ali; Hou, Deyi; Sarmah, Ajit K.; Moreno-Jiménez, Eduardo
Abstract: Biochar is a promising immobilizing agent of trace elements (TEs) in contaminated soils. However, several contradictory results have been reported regarding the potential of biochar to immobilize arsenic (As), chromium (Cr), and nickel (Ni) in contaminated soils. We conducted a meta-analysis on the published papers since 2006 until 2019 to examine the effects of biochar on the chemical (im)mobilization of As, Cr, and Ni in contaminated soils and to elucidate the major factors that control their interactions with biochar in soil. We synthesized 48 individual papers comprised of a total of 9351 pairwise comparisons and used the statistical tool of Cohen's d as an appropriate effect size for the comparison between means. We found that the application of biochar often increased the As mobilization in soils. Important variables that modulated the biochar effects on As mobilization in soil were pyrolysis temperature and time (ranging between 8 and 16 times when T > 450 °C and t > 1hr), organic matter (7–16 times when SOM<3%) and further site conditions. In contrast to As, biochar efficiently immobilized Cr and Ni in contaminated soils. The extent of the Cr and Ni immobilization was determined by the feedstock (Cr: 7–18 times for agricultural residue-derived biochar; Ni: 13–32 times for woody biomass-derived biochar). Our meta-analysis provides a compilation on the potential of different types of biochar to reduce/increase the mobilization of As, Cr, and Ni in various soils and under different experimental conditions. This study provides important insights on factors that affect biochar's efficiency for the (im)mobilization of As, Cr, and Ni in contaminated soils. While biochar effectively immobilizes Cr and Ni, a proper management of As-polluted soils with pristine biochar is still challenging. This limitation might be overcome by modification of biochar surfaces to exhibit higher surface area and functionality and active sites for surface complexation with TEs. Graphical abstract: Image 1 Highlights: Biochar immobilized Cr and Ni in soil. Biochar produced >450 °C exhibited high As mobilization in soils. The best feedstock for Ni immobilization was wood. The worst feedstock for Ni immobilization was agricultural residues and sewage sludge. Biochar for Cr and Ni immobilization was efficient in acidic humus poor soils.